Computer programs for handling nucleic acid sequences. - Keller, C (1984)
Programs have been developed that will accurately display restriction enzyme maps, open translational reading frames and the results of specific searches on a high resolution graphics terminal (Retrographics VT640). Many of our earlier programs have been upgraded to allow online access to GENBANK, the NIH data bank of DNA sequences and also to deal with sequences of any length. Progress has also been made in the automation of the DNA assembly programs.